PENGEMBANGAN KURIKULUM BERBASIS BUDAYA LITERASI MENYONGSONG GENERASI EMAS - Sumarni, Yayuk; Fitri Puji Rahmawati; Anik Ghufron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to evaluate the development of a literacy culture-based curriculum in primary schools. A qualitative approach with a case study method was used to gain an in-depth understanding of the process and dynamics of implementing the curriculum. Research Location at SD Negeri 03 Pandeyan, Tasikmadu, Karanganyar. Data were collected through in-depth interviews with teachers, students, principals and parents, classroom observations and analysis of curriculum documents. The results showed that primary schools have integrated literacy elements into various subjects using storybooks, folktales and local reading materials. However, more comprehensive and continuous training for teachers, particularly in digital literacy, is still needed. The establishment of literacy communities such as reading groups and weekly literacy activities has proven effective in increasing students' interest in reading. Collaboration with libraries, cultural organisations and local communities also contributes significantly to enriching students' literacy experiences. However, the use of digital technology in learning is still limited, especially in areas with minimal access to technology. Suggestions include improving teacher training, utilisation of digital technology, strengthening literacy communities in schools and increasing collaboration with stakeholders. With the right strategies and adequate support, a literacy culture-based curriculum can help produce a generation that is ready to face global challenges and contribute positively to society.